Context of coastal landscape development in Jūrmala - Īle, Una; Ozola, Reičela (Landscape Architecture and Art, 2025)
The study examines the coastal landscape of Jūrmala as a sustainable public outdoor space, ensuring seasonal accessibility and a modern identity in the context of the beach and coastline. The spatial structure of the coastal and beach areas was studied, including the beaches and coastal areas of Bulduri, Dzintari, Majori, Dubulti, Jaundubulti, Pumpuri, Melluži, Asari, Vaivari, and Kaugurciems. Historical information was researched and the coastal and beach area was surveyed in the present day, obtaining an assessment of public outdoor spaces. Based on the data obtained from the research, coastal and beach development measures were created.